Cover Image. Issue 12 (1st November 2020) - Chen, Siyu; Yang, Kou; Leng, Xuanye; Chen, Musen; Novoselov, Kostya S; Andreeva, Daria V
Abstract : The cover image is based on the Review Perspectives in the design and application of composites based on graphene derivatives and bio‐based polymers by Siyu Chen et al., https://doi.org/10.1002/pi.6080 . Illustration by Diego Pitta de Araujo. Abstract : The cover image is based on the Review Perspectives in the design and application of composites based on graphene derivatives and bio‐based polymers by Siyu Chen et al., https://doi.org/10.1002/pi.6080 . Illustration by Diego Pitta de Araujo.